Defensive Behavior and Morphometric Variation in Apis mellifera Colonies From Two Different Agro-Ecological Zones of North-Western Argentina - Bianchi, Eliana; Agra, Marcelo Nicolás; García, Cristina; Gennari, Gerardo; Maldonado, Luis; Rodríguez, Graciela Adriana; Palacio, María Alejandra; Scannapieco, Alejandra Carla; Lanzavecchia, Silvia Beatriz (Frontiers in Ecology and Evolution, 2021)
European lineages of Apis mellifera have been introduced into America for beekeeping purposes. Subsequent hybridization events with African lineages gave rise to Africanized populations which rapidly spread throughout the continent. Africanized populations have been detected mostly in northern regions of Argentina, and they represent a valuable genetic resource for the selection of promising stocks for beekeeping. The objective of the present study was to perform an integral characterization of honey bee colonies of wild origin with potential beneficial traits for apiculture. These colonies are located in two different agroecological environments of north-western Argentina (Tucumán province): Leales apiary in the Chaco Depressed Plain and Famaillá apiary in the Piedmont. The honey bee colonies from each apiary were surveyed in three times during the 2017-2018 season for brood population, phoretic Varroa and defensive behavior (run, fly, sting and hang). In addition, traditional and geometric morphometry (45 variables) and a genetic characterization of the apiaries by mitochondrial haplotype (COI-COII intergenic region) were performed at middle-beekeeping season. We observed similar dynamics for colony characteristics throughout the season. However, a significant variation in defensive behavior parameters was found between apiaries and times of inspection. In addition, significant differences were detected between the apiaries in terms of morphometric variables. Our results also showed a high representation of African A4 and A1 haplotypes (91%) in both apiaries. A multivariate analysis (PCA) including morphometric, genetic, and behavioral variables explained 53.5% of the variability observed between apiaries. Morphometric and defensive behavior variables explained mostly the distribution of the colonies from each apiary in the PCA two-dimensional space, showing distinctive profiles possibly related to the adaptation of honey bee colonies to the differential agroecological conditions. We discuss how the variation detected between apiaries contributes with tools for selection and preservation of honey bee ecotypes by breeding programs. The selected materials displaying tolerance to colony diseases and low defensiveness will assist beekeepers in enhancing apiculture in subtropical regions of Argentina.